2016
DOI: 10.1037/pag0000068
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward older adults: A matter of cultural values or personal values?

Abstract: 'Attitudes toward older adults : a matter of cultural values or personal values?', Psychology and aging., 31 (1).pp. 89-100.Further information on publisher's website:Publisher's copyright statement:c 2016 APA, all rights reserved. This article may not exactly replicate the nal version published in the APA journal. It is not the copy of record. Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 60 publications
3
49
1
1
Order By: Relevance
“…With this stated, they also concluded that economic stress, certain legal responsibilities, and the burden of caregiving, causes young individuals to be somewhat resentful and negative toward the elderly. These types of findings seem to hold across a number of studies [6] [17]. North and Fiske (2015) described how even though Asian cultures are more collectivistic than Western cultures, and that they have a long tradition of filial piety, attitudes in the East are more negative overall.…”
Section: Literature Reviewmentioning
confidence: 87%
“…With this stated, they also concluded that economic stress, certain legal responsibilities, and the burden of caregiving, causes young individuals to be somewhat resentful and negative toward the elderly. These types of findings seem to hold across a number of studies [6] [17]. North and Fiske (2015) described how even though Asian cultures are more collectivistic than Western cultures, and that they have a long tradition of filial piety, attitudes in the East are more negative overall.…”
Section: Literature Reviewmentioning
confidence: 87%
“…In the priming condition, in turn, we used the revised version of the Portrait Values Questionnaire (PVQ5X; Schwartz et al, 2012) to prime individuals to their personal values, in accordance with prior research (Zhang et al, 2016). That is, participants first responded to the PVQ5X before judging the personality of the two target persons.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Personal values concerning perceptions of individual interests and relationship/obligation to others are a key determinant of an individual's attitude toward the generational contract (Daatland, Veenstra, & Herlofson, 2012; Peterson & Ralston, 2017; Zhang et al., 2016). In this context, agentic and communal values deserve attention.…”
Section: Age Competing Values and Generational Contractsmentioning
confidence: 99%
“…The collective is more important than the individual (Schwartz, 2006). These values are aligned with communal values that promote reverence for tradition; respect for fellow humans; mercy and pity for those, like seniors, who are in need (Yeh, Yi, Tsao, & Wan, 2013; Zhang et al., 2016). This mixture of general respect, filial piety, and communal values contributes to the positive attitude toward the elderly in Chinese society (Boduroglu, Yoon, Ting, & Park, 2006) and sustain the generational contract.…”
Section: Age Competing Values and Generational Contractsmentioning
confidence: 99%
See 1 more Smart Citation